2006
DOI: 10.1007/bf03175033
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of salt response among yeasts

Abstract: Forty-two yeast strains from 27 species belonging to seven genera, selected for their ability to grow in 10% NaCl, have been analysed for their resistance to salt concentrations up to 5 M, by calculating the Minimum Inhibitory Concentrations (MIC). Using eight different NaCl concentrations from 0 to 5 M, results show that halotolerance (MIC) ranges from 1.7 to 3.8 M NaCl, with an average around 2.5 M and confirm that the most halotolerant strains belong to the species Debaryomyces hansenii. Since a real haloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…While these values are respectable, they do not indicate that they are halophilic and put these strains at the lower range of halotolerant yeasts. For example, Corte et al (2006) screened 27 halotolerant yeast species that can tolerate 10% NaCl and found that growth ceased at concentrations of between 1.7 and 3.8 M, with an average of 2.5 M. In addition, none of the Antarctic Naganishia species can grow in the presence of 10% NaCl, whereas about 30% of the non-Antarctic species listed in Barnett et al (2000) could grow in the presence of 10% NaCl.…”
Section: Ecological Tolerances Of Naganishiamentioning
confidence: 99%
“…While these values are respectable, they do not indicate that they are halophilic and put these strains at the lower range of halotolerant yeasts. For example, Corte et al (2006) screened 27 halotolerant yeast species that can tolerate 10% NaCl and found that growth ceased at concentrations of between 1.7 and 3.8 M, with an average of 2.5 M. In addition, none of the Antarctic Naganishia species can grow in the presence of 10% NaCl, whereas about 30% of the non-Antarctic species listed in Barnett et al (2000) could grow in the presence of 10% NaCl.…”
Section: Ecological Tolerances Of Naganishiamentioning
confidence: 99%
“…Exploring the ability of yeasts to tolerate salt concentrations (ionic stress) is important in industrial fermentations, where salt can favor yeast growth, enhance ethanol production, and at the same time, reduce the risk of contamination by microorganisms with low halotolerance (Corte et al, 2006). While S. cerevisiae was not able to grow in 5% NaCl, M. megachiliensis sustained its growth and displayed halotolerance up to 5% NaCl with no significant difference in absorbance compared to growth with at 0.5% and 1% NaCl.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the cheese is contaminated by an environment rich in yeasts when it is plunged in the brine. In particular, D. hansenii is resistant to the salt solution (Butinar, Santos, Spencer-Martins, Oren, & Gunde-Cimerman, 2005;Corte et al, 2006;Seiler & Busse, 1990) even if its presence, however, on the crust should not be considered a problem. In fact, this species is an important component in the production of several cheese type made with ewes' milk (Cosentino, Fadda, Deplano, Mulargia, & Palmas, 2001;Del Bove et al, 2009;Fadda, Mossa, Pisano, Deplano, & Cosentino, 2004;Gardini et al, 2006).…”
Section: Discussionmentioning
confidence: 99%